Efficiency Analysis of State-Owned Enterprise Bank Using Stochastic Frontier Analysis (SFA) Approach - Raihanah Ayu Nabila Gesti Putri; Erna Retna Rahadjeng; Sandra Irawati (Universitas Muhammadiyah Malang, 2022)
The purpose of the study was to determine the level of efficiency of state-owned banks for the 2019-2021 period. This research is a descriptive study with a quantitative approach that uses secondary data from the Financial Statements of State-owned Banks for the 2019-2021 period on the research object of PT. Bank Negara Indonesia Tbk., PT. Bank Rakyat Indonesia Tbk., PT. Bank Tabungan Negara Tbk., and PT. Bank Mandiri Tbk., obtained from the website of the Financial Services Authority. The data processed is data for the quarter of 2019 to the third quarter of 2021. The efficiency calculation is carried out using the Parametric Approach Stochastic Frontier Analysis which is processed using STATA 17. The results of the study using calculations show that state-owned banks in the 2019-2021 period have an average efficiency level of 0.9955 or close to 1. The results of these calculations indicate that state-owned banks are efficient in managing inputs into optimal output. State-owned banks that have the highest efficiency scores are Bank BRI and Bank Mandiri, followed by Bank BNI, then Bank BTN. State-owned banks still need to supervise managers and evaluate the allocation of deposits to productive assets to obtain greater profits to improve the overall economy.